Volatility in the transition markets of Central Europe - Kasch-Haroutounian, Maria; Price, Simon (Applied financial economics, 2001)
This study adds evidence from the four emerging markets of Central Europe relevant to the econometric modelling of financial time series by modelling volatility in these markets. The sample has all the previously documented characteristics of the unconditional distribution of stock returns normally used to justify the use of the GARCH class of models of conditional volatility. Both univariate and multivariate models are considered. Strong GARCH effects are apparent in all series examined. The estimates of asymmetric models of conditional volatility show rather weak evidence of asymmetries in the markets. The results of the multivariate specifications of volatility have implication for understanding the pattern of information flow between the markets. The constant correlation specification indicates significant conditional correlations between two pairs of countries: Hungary and Poland, and Hungary and Czech Republic. The BEKK model of multivariate volatility shows evidence of return volatility spillovers from Hungary to Poland, but no volatility spillover effects are found in the opposite direction.